Mental health of adolescents who abuse psychoactive substances in Enugu, Nigeria - A cross-sectional study - Igwe Wilson C; Ojinnaka Ngozi C (BMC, 2010)
Abstract Background Association between psychiatric morbidity and substance abuse among adolescent has been reported. However prevalence and pattern of such dysfunctions are unknown in our environment. Aims To determine the prevalence of psychosocial dysfunction and depressive symptoms among adolescents who abuse substance and also note the influence of socio-demographic factors and type of substance on the pattern of dysfuction. Method A cross-sectional study was carried out among 900 adolescents selected from 29 secondary schools in Enugu metropolis. A multi-stage sampling procedure was used to select the students. The student drug use questionnaire was used to screen respondents for substance abuse. Those who were abusing substance and matched controls (non substance abusers) were assessed for psychiatric symptoms using the 35-item Paediatric Symptom Checklist (PSC) and the Zung Self-rating Depression Scale (SDS). Social classification was done using the parental educational attainment and occupation. Result A total of 290 students were current substance abusers. The substances most commonly abused were alcohol (31.6%), cola nitida (kola nut) (20.7%) and coffee (15.7%). Using the PSC scale, 70 (24.1%) subjects compared to 29 (10.7%) of the controls had scores in the morbidity range of ≥ 28 for psychosocial dysfuction. This was statistically significant (χ2 = 17.57 p = 0.001). Fifty-four subjects (18.6%) had scores in the morbidity range of ≥ 50 for depressive symptoms using the Zung SDS compared to 21 (7.7%) of controls. This was statistically significant (χ2 = 14.43, p = 0.001). Prevalence of dysfunction was not significantly related to age in both subjects and controls (χ2 = 4.62, p = 0.010, χ2 = 4.8, p = 0.10 respectively). Also using both scales, there was no significant relationship between psychosocial dysfunction and gender or social class in both subjects and control. The prevalence of dysfuction using both scales was significantly higher in multiple abusers compared to single abusers. Subjects abusing alcohol scored more on both scales compared to those abusing other substances. Conclusion Prevalence of psychosocial dysfunction is higher in adolescents abusing substance compare to controls. The prevalence of psychiatric morbidity was not related to the age, gender or social classes in the study population.We advocate periodic screening of our adolescents for drug abuse regular evaluation of such group for possible psychopathology.